2019
DOI: 10.3390/s19102255
|View full text |Cite
|
Sign up to set email alerts
|

Towards Non-Invasive Methods to Assess Population Structure and Biomass in Vulnerable Sea Pen Fields

Abstract: Colonies of the endangered red sea pen Pennatula rubra (Cnidaria: Pennatulacea) sampled by trawling in the northwestern Mediterranean Sea were analyzed. Biometric parameters, such as total length, peduncle length, number of polyp leaves, fresh weight, and dry weight, were measured and related to each other by means of regression analysis. Ad hoc models for future inferencing of colonies size and biomass through visual techniques were individuated in order to allow a non-invasive study of the population structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Sea pens (subclass Octocorallia, order Pennatulacea) live on soft bottoms, from shallow to deep waters, and they can form dense aggregations known as sea pen fields which increase the complexity of an otherwise flat and monotonous seabed [76,77]. Pennatula rubra (Ellis, 1761) (Figure 1f), Pteroeides spinosum (Ellis, 1764) and Veretillum cynomorium (Pallas, 1766) are typical field-forming species of the continental shelf, being occasionally present form the euphotic zone but forming true fields only in the mesophotic [24,[78][79][80]. Pennatula phosphorea Linnaeus, 1758 and Virgularia mirabilis (Müller, 1776) can occur from mesophotic to deep seabed, often in mixed aggregation with other soft-bottom anthozoans, while Funiculina quadrangularis (Pallas, 1766) and Kophobelemnon stelliferum (Müller, 1776) represent deep-sea pennatulaceans able to form dense fields on the aphotic muddy bottoms [31,81,82].…”
Section: Sea Pen Fieldsmentioning
confidence: 99%
“…Sea pens (subclass Octocorallia, order Pennatulacea) live on soft bottoms, from shallow to deep waters, and they can form dense aggregations known as sea pen fields which increase the complexity of an otherwise flat and monotonous seabed [76,77]. Pennatula rubra (Ellis, 1761) (Figure 1f), Pteroeides spinosum (Ellis, 1764) and Veretillum cynomorium (Pallas, 1766) are typical field-forming species of the continental shelf, being occasionally present form the euphotic zone but forming true fields only in the mesophotic [24,[78][79][80]. Pennatula phosphorea Linnaeus, 1758 and Virgularia mirabilis (Müller, 1776) can occur from mesophotic to deep seabed, often in mixed aggregation with other soft-bottom anthozoans, while Funiculina quadrangularis (Pallas, 1766) and Kophobelemnon stelliferum (Müller, 1776) represent deep-sea pennatulaceans able to form dense fields on the aphotic muddy bottoms [31,81,82].…”
Section: Sea Pen Fieldsmentioning
confidence: 99%
“…Particularly, visual methodologies are more accurate and efficient for studying abundance of benthic populations in small areas (e.g. seapens), but they are often not appropriate for studying their biomass and size structure [59,61]. However, NEREIDA programme made substantive progress in the use of non-invasive sampling techniques to monitor VMEs in the NAFO Regulatory Area.…”
Section: Groundfish Surveys: Advantages Disadvantages Ethical Aspecmentioning
confidence: 99%
“…Chimenti et al [59,61] suggested that trawl data is still necessary to identify areas of high concentrations of cold-water corals (e.g. sea pen fields) at large scale, but ROV images could be used afterwards to monitor these concentrations in a non invasive way, consistent with the precautionary approach.…”
Section: Groundfish Surveys: Advantages Disadvantages Ethical Aspecmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not precise and not always easy to asses, the number of zooids can represent a valuable proxy for population structure in D. violacea considering that ascidians, like many other marine invertebrates (e.g. Chimienti et al 2018Chimienti et al , 2019b, can show a highly variable contraction state that makes size measurements ineffective. The asexual reproduction of D. violacea concerns solely the establishment and growth of the colony by increasing the number of zooids each years, but it does not generate further colonies.…”
mentioning
confidence: 99%